Issues and Challenges of Humanitarian Logistics in China - Rao, XiuHui Rebecca (2007)
This research discovers the existing challenges of humanitarian logistics in China in the event of NGOs responding to natural disasters. Humanitarian logistics has received rising interest from both the humanitarians and academic worlds, how to deliver supplies to the beneficiaries after a disaster to the right place, at the right time, with the right amount in an efficient manner is at the heart of humanitarian logistics. China such as one of the natural disaster frequently prone to countries, humanitarian logistics is an important skill that NGOs should embrace with in disaster relief operation as this will maximise their efficiency and effectiveness in operations. The existing literature suggests the possibility of cross learning between commercial supply chain and humanitarian supply chain, indeed, humanitarian supply chain is falling far behind its predecessor leaving a large gap for research and improvement. In completing this research work, two NGOs have been selected and agreed to give interview on helping the author to complete the work. The finding from the interview and the author's secondary research shows that humanitarian logistics is a relatively new term to be used in China, awareness and acknowledgement of this topic is weak in the humanitarians sector. NGOs in China respect the need to deliver supplies to people affected by disaster in an efficient manner, however, without knowing the foundational driver to improve delivery efficiency is rest in efficient logistics. The underdevelopment of humanitarian logistics in China blames to some challenges, some of these are improvable, while others are inherently existed therefore being difficult to overcome. The research contributes to discover some challenges in China that hindering the development and improvement of logistics in humanitarian relief operations, however, it does not provide formal recommendations to the problems, because this requires further research and in-depth knowledge into the situation of China and the development of humanitarian logistics in the international.